Pengaruh Pelatihan dan Motivasi Kerja terhadap Kinerja Pegawai dengan Kemampuan Kerja sebagai Variabel Intervening pada Dinas Tenaga Kerja dan Transmigrasi Kabupaten Tanjung Jabung Timur - Ariyanto Ariyanto (J-MAS (Jurnal Manajemen dan Sains), 2023)
This study aims to analyze the description of training, work motivation, employee performance and work ability at the Office of Manpower and Transmigration of East Tanjung Jabung Regency and analyze the effect of training and work motivation on employee performance which is mediated by work ability at the Office of Manpower and Transmigration of Tanjung Jabung Regency East. The method used in this research is descriptive verification and quantitative methods. The data collection method in this study was a questionnaire. Questionnaire (questionnaire) is a list of written questions that have been formulated previously to be answered, usually in clearly defined alternatives. The population in this study were all employees with civil servant status at the Office of Manpower and Transmigration of East Tanjung Jabung Regency during the period this study took place, namely as many as 60 people. In this study using saturation or census techniques because all the population, namely as many as 60 people were used as research samples. The analysis tool used is PLS analysis. Based on the description of training, work motivation, employee performance and work ability at the Office of Manpower and Transmigration of East Tanjung Jabung Regency, job training shows the trained category, work motivation shows the very high category, work ability shows the very high category and employee performance shows the very good category . The results showed that training had no significant effect on employee performance, work motivation had a positive and significant effect on employee performance, work ability had no significant effect on employee performance, training had a significant effect on work ability, work motivation had a significant and positive effect on work ability, training had no effect significant effect on employee performance, work motivation has no significant effect on employee performance.